2012
DOI: 10.1007/s00439-012-1141-y
|View full text |Cite
|
Sign up to set email alerts
|

A multi-ethnic study of a PNPLA3 gene variant and its association with disease severity in non-alcoholic fatty liver disease

Abstract: The adiponutrin (PNPLA3) rs738409 polymorphism has been found to be associated with susceptibility to non-alcoholic fatty liver disease (NAFLD) in various cohorts. We further investigated the association of this polymorphism with non-alcoholic steatohepatitis (NASH) severity and with histological features of NAFLD. A total of 144 biopsy-proven NAFLD patients and 198 controls were genotyped for PNPLA3 gene polymorphism (rs738409 C>G). The biopsy specimens were histologically graded by a qualified pathologist. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 36 publications
2
70
1
2
Order By: Relevance
“…Zain and Mohamed, demonstrated a significant association between the GG genotype and the fibrosis stage (p = 0.038); patients with GG genotype had a greater mean score of 2.03 compared to those with the CC genotype who had a mean score of 1.52. This association between the risk allele G of the rs738409 and the fibrosis stage, however, could not be assessed in the present study because only 3 patients with NASH had fibrosis [36].…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Zain and Mohamed, demonstrated a significant association between the GG genotype and the fibrosis stage (p = 0.038); patients with GG genotype had a greater mean score of 2.03 compared to those with the CC genotype who had a mean score of 1.52. This association between the risk allele G of the rs738409 and the fibrosis stage, however, could not be assessed in the present study because only 3 patients with NASH had fibrosis [36].…”
Section: Discussioncontrasting
confidence: 45%
“…This finding does not agree with the findings of Speliotes et al and Hotta et al who reported that the G allele of the rs738409 was significantly associated with decreased triglycerides levels in NAFLD patients but not in the control subjects and that this may be explained by decreased production of triglycerides due to the severity of NASH fibrosis [37] [41]. Moreover, in a study by Zain and Mohammed, the triglycerides levels and the G allele frequency were found to be higher in NASH patients without significant fibrosis compared to NASH patients with significant fibrosis [36]. The variation in our study can thus be explained by the fact that only 3 out of 46 patients with NASH had significant fibrosis and therefore strongly supports the suggestion by Jou et al that the triglycerides level drops with the extent of hepatocellular injury [42].…”
Section: Discussionmentioning
confidence: 94%
“…1C). PNPLA3 genotypes are associated with histologic severity of NAFLD (Sookoian and Pirola, 2011) and susceptibility to NASH (Zain et al, 2012). In the NAFLD cohort, carriers of the risk PNPLA3 (rs738409) G allele tended to have lower 4b-OHC concentrations, although the association was not statistically significant (Supplemental Fig.…”
Section: Cyp3a Activity and Expression Are Decreased In Nafldmentioning
confidence: 98%
“…The rs738409 variant similarly confers risk for increased histological severity dissociated from its effects on central obesity and IR [157,158] . Its pathogenic role in impaired lipid homeostasis as evidenced by a peripheral decrease in serum triglyceride, total and high-density lipoprotein cholesterol [159,160] is furthermore unmasked in the presence of increased visceral adiposity [161] and impaired glucose tolerance [162] , in addition to being modulated by lifestyle and dietary habits [161,163] . It has further been proposed that lipotoxicity and inflammatory stress resulting from impaired intra-hepatic lipid metabolism and free cholesterol deposition associated with PNPLA3 rs738409 activates dormant hepatic stellate cells (HSCs), leading to increased fibrogenesis.…”
Section: Incorporation Of Personalized Genomic Testing To Existing Comentioning
confidence: 99%